Development of Learning Media Assisted by Smart Apps Creator Application in Islamic Education Subjects in Senior High Schools - Hayati, Rifdha; Sari, Milya; Hasnah, Radhiatul; Remiswal, Remiswal; Fitriza, Rozi; Batubara, Juliana (Ahlussunnah: Journal of Islamic Education, 2025)
This research aimsto develop a product in the form of Android-based learning media assisted by the Smart Apps Creator application which is valid, practical and effective and focuses on increasing students' learning motivation.This research uses the methodR&D with the ADDIE model (Aanlyze, Desaign, Development, Implementation, Evaluation), which was held on June 4, 2025 at SMA N 1 Ampek Nagari Class X. Data at this stageAnalyze obtained through interviews, at the level Design done early planning, at the level Development data collected through the results of the Validity test on the material, media and language aspects, at the stageImplementation Data was collected through practicality tests on teachers and students (small scale and large scale), at the stageEvaluation Data was obtained from the effectiveness of increasing student learning motivation based on the Pre-Test and Post-Test using N-Gain.Research resultin the form of a series of product development processes for learning media assisted by the Smart Apps Creator application in the PAI subject for class X at SMA N 1 Ampek Nagari. Validity in the material aspect obtained a score of 94%, in the media aspect obtained a score of 94% and in the language aspect obtained a score of 95%. The small-scale practicality test obtained a score of 96%, in the large-scale test obtained a score of 97%, and the teacher's practicality test obtained a score of 96%. The effectiveness test based on the Pre-Test and Post-Test using N-gain showed an average N-Gain result of 77% which is in a larger interpretation of 76% which can be said that the learning media assisted by the Smart Apps Creator application in the PAI subject is proven to be effective and able to increase learning motivation in students.